2021
DOI: 10.33448/rsd-v10i6.15553
|View full text |Cite
|
Sign up to set email alerts
|

Nível de atividade física e comportamento sedentário de estudantes de educação física

Abstract: O objetivo do presente estudo foi analisar a associação entre o nível de atividade física e o comportamento sedentário de estudantes de Educação Física de uma faculdade da Zona Oeste do Estado do Rio de Janeiro. Para isso um grupo amostral com 90 estudantes, sendo 56 do sexo masculino e 34 do sexo feminino foi formado por conveniência. Todos os sujeitos responderam ao Questionário Internacional de Atividade Física e foram categorizados como satisfatoriamente ativos ou insatisfatoriamente ativos, bem como, tive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…It was also found that men and women spent more hours in sedentary behavior five days a week than on the weekend, which may be directly related to the long duration of classes, study, and academic work 23 .…”
Section: Discussionmentioning
confidence: 96%
“…It was also found that men and women spent more hours in sedentary behavior five days a week than on the weekend, which may be directly related to the long duration of classes, study, and academic work 23 .…”
Section: Discussionmentioning
confidence: 96%